Occurence and antibiotic resistance of Salmonella spp. isolated from eggs of chicken raised under free-range and conventional caged farms - Azihi, Siti Noor Fadhilah (2016)
Free-range and conventional caged farming systems implement different practices in raising their chicken;and therefore this could contribute to differences in the Salmonella and other bacterial contamination levels of eggs. The objective of this study was to determine the occurrence of Salmonella in eggs produced by free-range chickens and commercial layers. The isolates were then subjected to an antibiotic sensitivity test to determine the antibiotic resistance pattern.A total number of 36 free-range chicken eggs were purchased from three free-range chicken farms and another 36 commercial chicken eggs were purchased from three conventional farms raising chickens in battery cages. Salmonella spp. occurred in 2.8%(1/36 shell swab sample) and 8.4% (1/36 shell swab and 2/36 egg content samples) of conventional caged and free-range chicken eggs, respectively. Chi-square test showed significant association between farming system and level of Salmonella contamination in shell swabs and egg contents (p < 0.05). The one isolate from conventional caged chicken eggs was resistant to ampicillin. Two isolates (66.7%) from free-range chicken eggs were resistant to nalidixic acid, and 33.3% resistant to tetracycline,streptomycin, and trimethoprim- sulphamethaxzole. The pattern of antibiotic resistance of isolates from eggs obtained from free-range chickens' eggs and those from conventional caged was different. This study suggested that eggs from both production systems may not be as wholesome because of the presence of Salmonella, although low in number, but it is of public health significance.